Role of Key Metabolic Enzymes in Obesity-Associated Insulin Resistance: A Biochemical Review - Alaa R. M. Chyad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Obesity represents a critical global health challenge, serving as a primary risk factor for type 2 diabetes mellitus and insulin resistance through complex metabolic alterations. Specific Background: The pathophysiological mechanisms linking obesity to insulin resistance involve dysregulation of key metabolic enzymes that govern glucose and lipid homeostasis in insulin-sensitive tissues, including liver, skeletal muscle, and adipose tissue. Knowledge Gap: Despite recognition of enzyme involvement in obesity-related metabolic dysfunction, the precise biochemical pathways through which specific enzymatic networks contribute to insulin signaling disruption remain incompletely characterized. Aims: This review systematically examines the roles of major metabolic enzymes—including phosphoinositide 3-kinase, AMP-activated protein kinase, glucokinase, pyruvate dehydrogenase, carnitine palmitoyltransferase I, and acetyl-CoA carboxylase—in mediating obesity-associated insulin resistance. Results: Evidence demonstrates that obesity induces coordinated dysregulation across glycolytic, gluconeogenic, lipogenic, and oxidative pathways, promoting ectopic lipid accumulation, mitochondrial dysfunction, oxidative stress, and chronic low-grade inflammation that collectively impair insulin receptor signaling cascades. Novelty: This synthesis provides an integrated biochemical framework connecting enzyme-mediated metabolic flux alterations to systemic insulin resistance. Implications: Understanding these enzyme-specific pathways offers potential therapeutic targets for pharmacological intervention aimed at restoring insulin sensitivity and preventing metabolic complications in obese populations.Keywords : Obesity, Insulin Resistance, Metabolic Enzymes, Glucose Metabolism, Lipid MetabolismHighlight : Dysregulated lipogenic and oxidative enzymes drive ectopic lipid accumulation in insulin-sensitive tissues. Mitochondrial dysfunction and enzyme-mediated redox imbalance exacerbate metabolic inflexibility during obesity. Targeted modulation of key metabolic enzymes offers therapeutic potential for restoring insulin sensitivity.